2019
DOI: 10.4314/ejst.v11i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Optimum rate of NPS fertilizer for economical production of irrigated onion (Allium cepa L) in Dembyia District of Amhara Region, Ethiopia

Abstract: Onion is one of the most important vegetable crops grown under irrigation in Amhara Region. Application of fertilizer is an important input to increase yields of vegetables including onion where its rate mostly depends on the fertility status of the particular soil. The present study was initiated with the objective to identify the optimum rate of the newly introduced NPS fertilizer for maximum bulb yield of onion under irrigated smallholder farming system. The study was conducted in Dembyia District during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…e increase in the growth parameters of P. granatum with increase in the amount of nitrogenous fertilizer is in line with the works of Khalid and Shedeed [14] who explained that the application of the nitrogenous fertilizer coupled with foliar nutrition significantly improved the growth of Nigella sativa. Working with Allium cepa within the Amhara region of Ethiopia, similar observation was reported [15], stating that the application of a nitrogenous (NPS) fertilizer improved the overall growth parameters (number of leaves, leaf area, and height of plants) of the plant between 0.09 g NPK kg −1 soil and 0.13 g NPK kg −1 soil compared to the control experiment. ese improvements of the growth parameters of the plant, P. granatum, due to NPK application could be traced to the essential functions, and these elements serve in cellular enzyme activation [6,14] and the synthesis of proteins, nucleic acids, lipids, chlorophylls [5], and ATP [7].…”
Section: Discussionsupporting
confidence: 70%
“…e increase in the growth parameters of P. granatum with increase in the amount of nitrogenous fertilizer is in line with the works of Khalid and Shedeed [14] who explained that the application of the nitrogenous fertilizer coupled with foliar nutrition significantly improved the growth of Nigella sativa. Working with Allium cepa within the Amhara region of Ethiopia, similar observation was reported [15], stating that the application of a nitrogenous (NPS) fertilizer improved the overall growth parameters (number of leaves, leaf area, and height of plants) of the plant between 0.09 g NPK kg −1 soil and 0.13 g NPK kg −1 soil compared to the control experiment. ese improvements of the growth parameters of the plant, P. granatum, due to NPK application could be traced to the essential functions, and these elements serve in cellular enzyme activation [6,14] and the synthesis of proteins, nucleic acids, lipids, chlorophylls [5], and ATP [7].…”
Section: Discussionsupporting
confidence: 70%
“…(16.00 and 16.46 t/fed), while application of 25% of mineral NPK gave lowest values (12.68 and 13.64 ton/fed), in the first and second seasons respectively. Similar results were reported by Tekeste et al,(2018) and Nigatu et al,(2018) who reported that onion plants supplied with 105:119.6:22 kg ha-1 N:P2O5:S fertilizer rate gave the highest mean marketable yield (20.8ton ha-1).…”
Section: B2 Exportable Bulbs Yield (Ton/fed) 1 Mineral Npk Ratessupporting
confidence: 89%
“…Significantly lower bulb diameter observed in the control plot, whereas statistical difference was not observed between all fertilizer treatments. In line with this (Nigatu et al, 2018) and (Gebremichael et al, 2017) reported that bulb diameter measured from non-fertilized plots was lowest compared to the plots treated by integrated application inputs.…”
Section: Plant Height and Bulb Diametersupporting
confidence: 66%
“…Despite this, productivity of the crop remains low 10.02 t ha -1 (FAO, 2012). The average annual onion production in Ethiopia is about 230,745.2 tons with the productivity of about 9.5 t ha -1 (Nigatu et al, 2018). In Ethiopia, onion is very important in the food interest and in daily stews as well as in different vegetable food preparation uses.…”
Section: Introductionmentioning
confidence: 99%